(untitled) (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
This study aims to explore and analyze the implementation of the Project to Strengthen the Profile of Pancasila Students based on local wisdom through Pencak Silat’s extracurricular activities in elementary schools. The primary focus of the research is to understand the planning, implementation, evaluation, and character outcomes of students following this program. The research method used is qualitative with a descriptive approach. The main informants include the school principal, Pencak Silat teachers, students, and parents. Data were collected through interviews, observations, and document analysis. The results of the study indicate that the project to strengthen the profile of Pancasila students’ program planning has been well-structured, identifying relevant local wisdom values to be taught to students. Regular evaluations are conducted to monitor student progress in aspects of discipline, responsibility, and respect, with results showing a significant improvement in students’ character after participating in this program. The conclusion of this study suggests that the project to strengthen the profile of Pancasila students program based on local wisdom through Pencak Silat extracurricular activities is effective in developing students’ character in line with the Profile of Pancasila Students. Recommendations for this research include strengthening teacher training, creating learning materials, and integrating the program into the school curriculum to expand its positive impact. Further research is recommended to measure the long-term effects of this program on students’ character development and the integration of local wisdom values in formal education.